Dampak Covid-19 Terhadap Ekonomi dan Sumber Daya Manusia - Setiawati Ningsih; Shandra Ziva Hendriani; Ricky Firmansyah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2022)
The virus called coronavirus disease 2019 (Covid-19) has attacked many countries and is growing rapidly, including Indonesia. On March 2, 2020, his first case of Covid-19 in Indonesia was officially recognized, and as it affects many factors, especially the industrial sector and the human resources sector, the government and the World Health Organization (WHO) must take action. Rapidly adopt new guidelines we create to combat Covid-19. The purpose of this study was to analyze the economic and human resource impact experienced by her 47 respondents who were active as clerical class students at the University of Digital Technologies. This study used a descriptive quantitative method in which the data obtained were obtained from the results of an online survey via Google Forms. Study results show the extent to which Covid-19 will impact existing economies and human resources.